Evolutionary parasitology the integrated study of infections, immunology, ecology, and genetics - Schmid-Hempel, Paul (Oxford Oxford University Press, 2011)
From the publisher. Parasites are everywhere. And they affect almost every aspect imaginable in the life of their hosts. Parasites influence host physiology, behavior, life histories, and the structure of entire ecosystems. To cope with these constant threats, the host's immune system has evolved to become one of the most complex organs known. But parasites, too, have found their own ways to overcome defences and to manipulate their hosts for their own interests. As a result, hosts and parasite are constantly forced to adapt to one another, sometimes very rapidly, sometimes changes occur only over eons. But this struggle always has far reaching consequences for the biology of both parties. For the first time, this book gives a comprehensive overview over the many facets of host-parasite interactions, from the molecular bases to individual strategies and to the ecological and evolutionary consequences. It is informed by the progress in our understanding that has occurred over the past decades. No longer do we view well-adapted parasites to become harmless but, quite to the contrary, parasite virulence is, determined, both, by the processes that lead to harm and by the evolutionary costs and benefits of this damage. Similarly, parasitism is no longer regarded as being inevitably bad, rather it can be a major factor maintaining diversity in populations and communities, selecting for beautiful plumages of birds, or making us more social. Evolutionary Parasitology deals with a wide range of topics, from immunology, genetics, sexual selection, to population dynamics, ecology and co-evolution. Readers from different fields and with different backgrounds will find a rich source to meet their interests and to expand their insights into neighbouring disciplines.
1. Parasites and humans -- Mission impossible -- Some lessons by yellow fever -- Parasites in our times -- 2. The study of evolutionary parasitology -- The evolutionary process -- Questions about host-parasite interactions -- Selection and units that evolve -- Life history -- Studying adaptation : optimality and evolutionarily stable strategies (ESS) -- Comparative studies -- 3. The diversity and natural history of parasites -- The ubiquity of parasites -- A systematic overview of parasites -- The evolution of parasitism -- The diversity and evolution of parasite life-cycles -- 4. The natural history of defences -- The defense sequence -- Defense by the immune system -- Basic elements of the immune defense -- Immune defense protein families -- The generation of diversity in recognition -- The diversity of immune defenses -- Evolution of the immune system -- 5. Ecological immunology -- Variation in parasitism -- Ecological immunology : the costs of defense -- The nature of defense costs -- 'Immunocompetence' and the benefits of defense -- Strategies of immune defense -- Tolerance as defense element -- 6. Parasites, immunity, and sexual selection -- Differences between the sexes -- Parasites and sexual selection -- Sexual selection and immunity in invertebrates -- 7. Specificity -- Measuring specificity and host range -- Host-specificity of parasites -- Evolution of the host range -- Specific defenses of the host -- Memory, immune priming, and trans-generational transfer -- Adaptive diversity and cross-reactivity -- 8. Parasite immune evasion and manipulation of host phenotype -- Parasites manipulate their hosts -- The diversity of immune-evasion mechanisms -- Manipulation of the host phenotype to increase transmission -- Manipulation of the host phenotype to increase infection lifetime -- Mechanisms of host phenotype manipulation -- Strategies of manipulation -- Ecological significance of manipulation -- 9. Infection and pathogenesis -- Infection and dose -- Similar parasites cause different pathologies -- Pathogenesis : the mechanisms of virulence -- Immunopathology -- The genetics of pathogenesis -- 10. Host-parasite genetics -- The genetic architecture of host resistance -- Evolutionary genetics of host-parasite interactions -- Signatures of selection -- Genetic structure of protozoan parasites -- 11. Epidemiology -- Population biology of host-parasitoid systems -- Epidemiology of infectious diseases : microparasites -- Endemic infections and periodic outbreaks -- Epidemiology of vectored microparasites -- Epidemiology of macroparasites -- Immuno-epidemiology -- Epidemiology with evolutionary change -- Within-host epidemiology -- 12. Virulence -- Virulence -- The evolution of virulence -- Concepts of virulence evolution -- Within-host evolution -- Life history of infection events -- Within- vs. between-host selection -- Host population structure -- Non-equilibrium virulence -- 13. Host-parasite (co-)evolution -- Macro-evolution -- Micro-evolution -- Micro-evolution : the maintenance of diversity -- Antagonistic co-evolution, sex, and recombination -- The evolution of sex and recombination under parasitism -- Selective sweeps -- 14. Ecology -- Parasites and host life-history -- Host populations -- Host ecological communities -- Parasite ecology -- Invasions.
Includes bibliographical references (pages 435-498) and indexes.
Keywords: Parasitism